An analysis of how knowledge is differentiated in a vocationally based curriculum for a new profession - Halliday, Linda (School of Education, 2015)
Inspired by Muller’s (2009) ‘Forms of Knowledge and Curriculum Coherence’ and his theories relating to types of knowledge and curricula differentiation, this study interrogates knowledge in a vocational qualification, asking how it is differentiated in a vocationally based curriculum intended for a new ‘fourth generation’ profession (as opposed to ‘first generation’ professions such as medicine or engineering). The study specifically examines and compares two recontextualising processes; a vocational, unit-standards-based qualification intended for the fitness profession and its curriculum that is designed to meet the qualification’s requirements. The analysis reveals the type of knowledge developed in both. According to Muller (2009), market-related shifts have given rise to many new professions – fourth generation professions - which he claims lack the epistemic foundation of traditional disciplines. To meet the growing demand for these emerging professions, institutions of higher education are being asked to make knowledge and skills more accessible through a range of sector-based, vocational and higher education pathways, leading to clearly-defined outcomes. According to Wheelahan (2007), reducing knowledge to observable outcomes or competencies simply produces a ‘fragmented and atomistic view of knowledge’. Thus, the concern is about knowledge and the call from many educational sociologists is for ‘powerful knowledge’; that increases access, encourages cumulative learning and enables its transferability (Young, 2008a, Wheelahan, 2007). Acknowledging the socio-epistemic nature of knowledge, this study focuses on the epistemic, exploring different types of knowledge in a vocationally based higher education setting. Working within the recontextualising field of Bernstein’s (2000) Pedagogic Device, the study explores types of knowledge and the organising principles that constitute knowledge practices within a South African vocational educational setting. Of particular interest to the study are ways in which conceptual knowledge increases through a process of concept-integration, and whether or not such knowledge informs practice. The analysis calls upon Maton’s (2000) Legitimation Code Theory (LCT), specifically LCT Semantics, to explore meanings in curriculum texts in order to identify different types of knowledge. In using LCT Semantics, conceptual and practice-based knowledge is identified and graded according to differing levels of conceptual complexity and context-dependence. While the analysis exposes a range of theoretical knowledges, from simple to relatively complex concepts which emanate from the disciplines that form exercise science, it also explains the nature of contextually based knowledge, shaped by the demands of vocational practice (Muller, 2009, Shay, 2013). This study reveals that, despite the segmental nature of its unit-standards-based qualification, it is possible for vocational curricula to ensure concept-building, while being informed by its vocational requirements.